Tricuspid annular and right atrial volume changes are associated in healthy adults—insights from the three-dimensional speckle-tracking echocardiographic MAGYAR-Healthy Study - Nemes, Attila; Kormányos, Árpád; Rácz, Gergely; Ruzsa, Zoltán; Achim, Alexandru; Ambrus, Nóra; Lengyel, Csaba (Frontiers in Cardiovascular Medicine, 2023)
Introduction. The tricuspid valve and its annulus (TA) and the right atrium (RA) play a significant role in regulating blood flow in the right heart. However, their effect on each other is not fully understood even in normal circumstances. Three-dimensional (3D) speckle-tracking echocardiography (3DSTE) is able to simultaneously assess TA and RA at the same time in a non-invasive way. The present study aimed to examine associations between tricuspid annulus (TA) dimensions and right atrial (RA) volumes in healthy adults by 3DSTE.Methods. The present study comprised 144 healthy subjects (mean age: 34.4 ± 12.6 years, 72 males), who participated in this study on a voluntary basis for screening between 2011-2015.In all subjects, electrocardiography, two-dimensional Doppler echocardiography and 3DSTE have been performed.With increasing end-systolic maximum RA volume, all end-systolic and end-diastolic TA dimensions showed simultaneous increase, but in various degrees resulting in (nonsignificant) reduction of TA functional properties. Similarly, with increasing diastolic pre-atrial contraction and minimum RA volumes, TA dimensions increased simultaneously (except enddiastolic TA diameter), but in various degrees resulting in reduced TA fractional shortening and fractional area change. With increasing TA dimensions, end-systolic and end-diastolic TA dimensions showed simultaneous increase, but in different, sometimes not significant degrees.While RA stroke volumes showed increasing pattern with TA dilation, RA emptying fractions have not changed substantially.Conclusions. 3DSTE is suitable for non-invasive assessment of TA dimensions and RA volumes at the same time using the same 3D echocardiographic dataset. Significant associations between TA size and RA volumes exist in healthy circumstances. Strong associations in case of dilation of TA in the presence of higher RA volumes could partly explain functional tricuspid regurgitation later developing in subjects in sinus rhythm.